Negative reinforcement as shock-frequency reduction - Herrnstein, R. J. (1966)
Is a conditioned aversive stimulus necessary in avoidance conditioning? Or is a reduction in the rate of aversive stimulation alone sufficient to generate and maintain an avoidance response? Rats were subjected to an avoidance procedure in which shocks occurred randomly in time, but a response could reduce the overall rate of shock. Fifteen acquisition curves, obtained from 16 animals, showed both immediate and delayed, rapid and gradual increases in response rate; there was no representative acquisition curve. Response rates were directly related to the amount by which the response reduced shock frequency. In extinction, when shock rates were not affected by responding, the response total was inversely related to the amount by which the response had reduced shock frequency during prior conditioning, with as many as 20,000 extinction responses when the shock frequency reduction had been relatively small. Responding on this procedure shows that avoidance conditioning can occur without benefit of either classical exteroceptive stimuli or covert stimuli inferred from the temporal constancies of a procedure. It also shows that reduction in shock rate is alone sufficient to maintain avoidance.